Turnover Intention: Influence of Job Insecurity and Job Satisfaction Among Contract Employees in the Technology Division - Shalsa Dela Nur Septi; Kustini Kustini (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2026)
Purpose - This study aims to analyze the effect of job insecurity and job satisfaction on turnover intention among contract employees in the technology division of PT. XYZ. The research seeks to understand how perceived job uncertainty and levels of job satisfaction influence employees’ intention to leave the organization. Design/methodology/approach – This study used a quantitative survey of all 48 contract employees in the technology division of PT. XYZ. The data were analyzed using Partial Least Squares (PLS) to examine the relationships between job insecurity, job satisfaction, and turnover intention. Originality -  This research offers new insights into turnover behavior among contract-based technology employees in Indonesia, a group often overlooked. Focusing on a project-driven tech division, it highlights the unique psychological and organizational challenges faced by contract workers. Findings and Discussion – The results show that job insecurity significantly increases turnover intention, especially threats to job aspects, while job satisfaction reduces it, with salary as the key factor. Short-term contracts and limited career growth raise employees’ desire to leave, whereas fair pay and recognition help lessen it. Conclusion – The study concludes that clearer contract renewal, better career development, and fair compensation can reduce turnover intention among contract employees. Open communication between management and staff is also essential to strengthen trust, job satisfaction, and loyalty.